Incidencia del capital social en el desarrollo local de la parroquia Mulalò - Pilco Sandoval, Héctor Darío (2017)
Trust within social capital fulfills an important role since that will allow local development based on cooperation between society and the authorities. Based on this principle was born the importance of this research. As principal objective was investigating the incidence of the social capital in the local development of Mulaló, diagnostic tools and a methodology presented for this purpose is used for which, it allowed to determine the influence of this capital on the local development of the sector. As base of the problem is identified a stagnation in the development of Mulaló both economic and social demonstrating it in the conditions of life of the inhabitants, which initiated the need for the implementation of the project. To facilitate the research is based in the theory centered of the needs of the same. Subsequently held the Situational diagnosis of the city in order to observe and establish the situation in which it is found with respect to different fields from education to economic development, noting flaws in the quality of life of the inhabitants, the basic services, in the development and the performance of the authorities. After perform the diagnosis is validated the hypothesis that posed that the confidence of the inhabitants towards their authorities influenced directly in the use of the resources endogenous that has the sector, being the confidence the dimension more important of the social capital and the resources which allow that there is a local development, and observing wheater are exploited what improves the quality of life of the inhabitants, with this present was established in statistical form using the chi-square test that this relationship exists between variables established laying the groundwork for the investigation. With the situational diagnostic made, the validation of the hypotheses made and the relation between the social capital and the local development established; is proceeded to define the unit of study that is raised used in the measurement of the social capital through a methodology that define the universe, the sample, the methods and techniques to use for that purpose. For the diagnostic was chosen the instrument that elaborate the World Bank that fit with the conditions of Mulaló, all this after having analyzed and compared with support of a bibliographical research jointly with a critical analysis was chosen between a wide variety of instruments.